IgA kappa/IgA lambda heavy/light chain assessment in the management of patients with IgA myeloma. Issue 24 (12th August 2014) - Boyle, Eileen M.; Fouquet, Guillemette; Guidez, Stéphanie; Bonnet, Sarah; Demarquette, Helene; Dulery, Remy; Herbaux, Charles; Noel, Marie Pierre; Manier, Salomon; Schraen, Suzanna; Onraed, Brigitte; Faucompré, Jean‐Luc; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Accurate quantification of immunoglobulin A (IgA) monoclonal immunoglobulins by serum protein electrophoresis (SPEP) can be difficult and can impact the assessment of response among patients with multiple myeloma (MM). Therefore, there is a need to identify new assays that better reflect disease burden and response to treatment, and correlate with patient outcome. IgA Hevylite (HLC) measures IgA kappa and IgA lambda separately and provides precise quantitative measurements of the monoclonal IgA expression and polyclonal‐isotype matched suppression. In the current study, the authors assessed the usefulness of these assays in the diagnosis of IgA MM and sought to comment on the prognostic value of the assays. METHODS A study of 157 patients with IgA MM for whom diagnostic samples were available was performed. HLC measurements were performed on a nephelometer and the results were compared with those of electrophoresis. RESULTS All presentation sera (100 IgA kappa specimens and 57 IgA lambda specimens) were found to have abnormal IgA HLC ratios (IgA kappa median ratio: 336.2 [range, 8.2‐7353] and IgA lambda ratio: 0.011 [range, 0.0003‐0.45]). In comparison, SPEP bands were quantifiable in only 105 of 157 samples (67%) (median, 28.5 g/L [range, 2.2 g/L‐98 g/L]). Of the total of 157 patients, 12 patients (8%) presented with oligosecretory myeloma (<10 g/L; including 4 patients with nonquantifiable SPEP bands). HLC uniquely allows for the measurement of isotype paired suppression, which was found to be associated with shortened overall survival in the current study. CONCLUSIONS In the current study, IgA HLC ratios were found to be abnormal in all patients and the assay was able to produce quantifiable results in more MM sera than either SPEP or total IgA, potentially representing a solution to the issue of comigration and oligosecretory MM. These preliminary data require confirmation in larger prospective trials to validate the usefulness of IgA HLC. Cancer 2014;120:3952–3957. © 2014 American Cancer Society.